Associations Between Candida and Staphylococcus aureus, Pseudomonas aeruginosa, and Acinetobacter Species as Ventilator-Associated Pneumonia Isolates in 84 Cohorts of ICU Patients - James Hurley (Microorganisms)
Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter species, and Candida species are common ventilator-associated pneumonia (VAP) isolates. Whilst the clinical significance of Candida as a VAP isolate is unclear, evidence is emerging that Candida interacts with bacteria, contributing to colonization susceptibility. Indirectly, VAP isolate data reflect patient colonization within cohorts. The objective here is to estimate the association between these three bacteria and Candida as VAP isolates. ICU cohorts were obtained by searching the literature for mechanically ventilated (MV) patient cohorts in which Candida was listed as an isolate among patients with VAP. Regression models of the associated VAP incidence per 100 MV patients, using random effects methods, incorporated group-level factors such as the year of publication, mode of VAP diagnosis, and ICU stay length. The median VAP incidence proportions for Staphylococcus aureus, Pseudomonas aeruginosa, and Acinetobacter species were 3.3 (IQR: 1.2–6.9), 3.6 (IQR: 1.8–5.7), and 1.2 (IQR: 0.4–4.1), respectively. Among 84 cohorts from 67 publications, Staphylococcus aureus (correlation coefficient = 0.759) and Pseudomonas aeruginosa (0.749), and less so Acinetobacter species (0.53), each show correlation with the isolation of Candida species among these ICU populations. These associations may underlie the poor prognosis with Candida colonization.